Earmarking Tax Optimization to Support The Effective and Sustainable Infrastructure - Sasana, Hadi (Universitas Muhammdaiyah Surakarta, 2017)
The majority of road infrastructure condition is far from excellent. The implementation of 10% minimum compulsory allocation of vehicle tax to be returned for road and transportation sector is potential to increase road maintenance fund.The research purpose is to raise regional revenue sources of Semarang City which is worth to be earmarked and to be alocated for road maintenance. This research is using secondary data of 2008-2015 period and linear regression analysis with Ordinary Least Square (OLS) method. The result of research concludes that : 1) the sources of earmarking consist of : vehicle tax (PKB), fee of vehicle title transfer (BBNKB), and fuel tax (PPBKB). 2) the allocation proportion of each earmarking source for Semarang City road maintenancefor next five years are : 25% (PKB), 15% (BBKNB), and 15% (PBBKB). 3) the allocation proportion of each earmarking source for Semarang City roadconstruction for next five years are: 50% (PKB), 45% (BBNKB), and 45% (PBBKB).Â